Evolving failures in the delivery of HIV care: Lessons from a Ugandan meningitis cohort 2006-2016 - Flynn, Andrew G; Meya, David B; Hullsiek, Katherine Huppler; Rhein, Joshua; Williams, Darlisha A; Musubire, Abdu; Morawski, Bozena M; Taseera, Kabanda; Sadiq, Alisat; Ndyatunga, Liberica; Roediger, Mollie; Rajasingham, Radha; et al. (In Open Forum Infectious Diseases, 2017)
Background: Investments in HIV care in sub-Saharan Africa have increased the number of people aware of their status and receiving antiretroviral therapy (ART), yet HIV/AIDS mortality remains high. Methods: We performed retrospective analysis of three sequential prospective cohorts of HIV-infected Ugandan adults presenting with AIDS and meningitis from 2006-2009, 2010-2012 and 2013-2016. Participants were categorized as: 1) unknown HIV status; 2) known HIV+ without ART; 3) known HIV+ with previous ART. We further categorized 2006 and 2013 cohort participants by duration of HIV-status knowledge and of ART receipt. Results: We screened 1353 persons with suspected meningitis. Cryptococcus was the most common pathogen (63%). Over the decade we observed an absolute increase of 37% in HIV status knowledge and 59% in antecedent ART receipt at screening. 2006 cohort participants were new/recent HIV diagnoses (65%) or known HIV+ but not receiving ART (35%). Many 2013 cohort participants were new/recent HIV diagnoses (34%) and known HIV+ with <1-month ART (20%), but a significant proportion were receiving ART 1-4 months (11%) and >4 months (30%). 4% discontinued ART. From 2010 to 2016, meningitis cases per month increased by 33%. Conclusions: While improved HIV screening and ART access remain much-needed interventions in resource-limited settings, greater investment in viral suppression and opportunistic infection care among the growing HIV-infected population receiving ART is essential to reducing ongoing AIDS mortality.
HIV care failures in Ugandans with AIDS
Keywords: HIV/AIDS; Antiretroviral therapy; HIV care continuum; Cryptococcal meningitis; Sub-Saharan Africa